Drug Therapy-related Problems Detected by Clinical Pharmacists in a Closed Loop Medication Management; A Cross-sectional Study in UAE - Farah Selim; Baig, Mirza; Mohamed Magoury; Waqar Ahmed; Mansour A. Mahmoud (Archives of Academic Emergency Medicine, 2024)
Introduction: Drug therapy-related problems (DTRP) can lead to avoidable negative health consequences, particularly during hospital admissions. This study aimed to assess the frequency, causes, and associated factors of DTRPs, which are detected by clinical pharmacists’ interventions. Methods: This is a prospective cross-sectional study of patients admitted to the medical wards of Fakeeh University Hospital, UAE, over a three-month period from September 2022 to December 2022. The data of patients who were assessed by clinical pharmacists regarding the pretense and causes of DTRPs were collected and analyzed using SPSS version 27.0. Results: 310 patients with the mean age of 33.43 ± 19.98 years were studied (53.9% male). The highest percentage of patients were Asian (31.0%) and Arabs (30.6%). 79 (25.4%) cases had no DTRPs, while 231 (74.6) had DTRPs. The surgical ward had the highest frequency of DTRPs (41.0%). Improper drug selection with 79 cases, drug use without indication with 73 cases, and sub-therapeutic dosage with 26 cases were among the most common causes of DTRPs. Alcohol intake (p= 0.03), food allergy (p = 0.02), age group 31-40 years (p = 0.04), presence of co-morbidities (p = 0.01), family history of diseases (p = 0.02), and admission to the intensive care unit (ICU) (p = 0.01) were amongst the significantly associated factors of DTRPs. The acceptance status for clinical pharmacists’ interventions were complete in 90.0% of cases, partial in 4.1 %, and rejection in 5.9%. Conclusion: The study findings show a high prevalence of DTRPs due to drug/dose selection and drug use without indication. It seems that the participation of clinical pharmacists in multidisciplinary teams together with the presence of closed loop medication management facilitates the detection and correction of DTRPs.